2010
DOI: 10.1007/s11661-010-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Fatigue Behaviors and Dislocation Structures in Interstitial-Free Steel

Abstract: There are three types of cyclic hardening for cyclically deformed interstitial-free (IF) steels. The magnitude of cyclic hardening was unobvious and dislocation cells smaller than 2 lm were very hard to find when total strain amplitude (De/2) was controlled to within 0.1 pct. When De/2 is increased to 0.125 to 0.3 pct, secondary cyclic hardening takes place prior to fatigue failure. De/2 = 0.6 pct, following an initial rapid-hardening stage. Dislocation cells smaller than 2 lm tend to develop near grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The softening response after initial hardening results from generation of additional mobile dislocations and formation of dislocation cell substructures of lowered internal stresses (Raman and Padmanabhan, 1994). According to Shih et al. (2010), secondary hardening rate and volume fraction of small dislocation cells are directly proportional with strain amplitude in interstitial-free steels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The softening response after initial hardening results from generation of additional mobile dislocations and formation of dislocation cell substructures of lowered internal stresses (Raman and Padmanabhan, 1994). According to Shih et al. (2010), secondary hardening rate and volume fraction of small dislocation cells are directly proportional with strain amplitude in interstitial-free steels.…”
Section: Resultsmentioning
confidence: 99%
“…According to Shih et al. (2009, 2010), while cyclic strain is controlled just above the fatigue endurance limit and cycled to failure, the small dislocation cells prefer to develop near the grain boundaries and at GBTPs for interstitial-free steels.
Figure 6. All Euler orientation (SEM-EBSD/OIM) micrographs showing polycrystalline austenite grains’ geometries, configurations and connectivity of (a) base alloy (reference) and cyclically deformed AISI 304LN stainless steel at different strain amplitudes: (b) ±0.50%, (c) ±0.70%, (d) ±0.85%, (e) ±1.0%, (f) ±1.2%, (g) ±1.4% and (h) ±1.6%.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of BEI is the sample preparation is easy and the observation region is broad. Huang et al [31,32] successfully observed the dislocation structure of copper and interstitial free (IF) steel regardless of the strain amplitude using this technique. The dislocation structure evolution in ultra-large grain (average grain size of about 600 mm) in pure copper is very seldom reported in the literature.…”
Section: Introductionmentioning
confidence: 99%